Analysis and Mathematical Application of Taylor Series to Crystallization of Rock forming minerals from Magma - Ifeanyi, Achuenu; Lekmang C. Isah; Hyeladi Dibal; Geoffrey Mica Kumleng (RADINKA JOURNAL OF SCIENCE AND SYSTEMATIC LITERATURE REVIEW, 2025)
Power series in magma is the power of a mineral to form from magma at a controlled condition of temperature or pressure and the process of mineral formation from magma using power series is called Taylor series in magma. The reactions in magma are very complex because of several anionic and cationic substitutions of different sizes and charges in the magma and in this case, complex problems require complex solutions. This research was focused more on using Bowen and Goldschmidt concepts concerning the elemental substitution and distribution of chemical elements in rocks throughout the time of crystallization with mathematical foundations such as Taylor series to predict major minerals, encompassing olivine, pyroxene, amphibole, mica, and feldspar, and their associated rocks, encompassing granite, basalt, andesite, and trachyte. Findings have shown that, in a mathematical context, Bowen’s and Goldschmidt rules were mathematically connected using the Taylor series.